A Comparison of Criminological and Public Health Models: Geographic and Social Diversity Associated with Methamphetamine Laboratory Seizures - Weisheit, Ralph A. (American journal of criminal justice, 2014)
In the 1990s methamphetamine (meth) emerged as a significant drug problem in the United States. Along with more widespread meth use was a growing pattern of localized production of the drug in small-scale clandestine laboratories, creating public health issues beyond the drug’s direct harms to the health of users. Early efforts in analyzing aggregate patterns of meth lab production across communities suggest this phenomenon is different from other types of crime and drug problems, showing distinctive geographic patterns and different causal/etiological dynamics. This paper assesses the viability of public health outcomes as predictors of methamphetamine laboratory problems and compares them with traditional criminological predictors as explanations for aggregate patterns in meth lab problems across U.S. counties. It documents how local variations in meth production are different from other types of crime patterns and identifies whether geographic variations in local meth labs might be more effectively predicted and explained in public health terms.